Development of 3D interconnected heterogeneous high-entropy alloy composites with enhanced multifunctionality via liquid metal dealloying - Munsu Choi; Gang Hee Gu; Jongun Moon; Jae Wung Bae; Hidemi Kato; Seung Zeon Han; Hyoung Seop Kim; Yongseok Choi; Soo-Hyun Joo (Journal of Materials Research and Technology)
Liquid metal dealloying (LMD) is a selective extraction method wherein miscible elements are removed from a precursor alloy to obtain a three-dimensional (3D) interconnected structure. This study presents a novel application of this method to fabricate heterostructured materials from a CoCrFeMnNi high-entropy alloy (CoCrFeMnNi HEA) precursor immersed in molten Cu at 1095 °C, and it elucidates complex dealloying and mutual alloying processes. Of the five constituent elements of the HEA precursor, Mn and Ni preferentially dissolved in the Cu melt, and interconnected Cu-rich melt channels were formed in the precursor. Simultaneously, Cu diffused into the CoCrFe-rich solid ligaments. The resulting heterostructured material, formed under local equilibrium conditions, comprised dual face-centered cubic (fcc) phases that were characterized by refined grain sizes and high interconnectivity. The transformation from precursor fcc grains to CoCrFe-rich fcc ligaments followed uncommon orientation relationships based on non-close-packed planes. Increases of 7 % and 82 % were observed in the hardness and electrical conductivity of the dual fcc heterostructured HEA, respectively, and they are attributed to the HEA's unique 3D interconnected microstructure. Density functional theory calculations indicated that effective multicomponent mixing contributed significantly to the observed electrical performance, which was superior to that of Cu-containing medium-entropy alloys with conventional microstructures. A key structural factor was the continuous Cu-rich fcc phase, which formed an extensive 3D conductive network to provide exceptional conductivity through the synergistic “cocktail effect.” These results highlight the potential of LMD to help achieve multifunctionality in HEA systems via the formation of heterogeneous microstructures.